Assessing the bond strength of hot mix asphalt pavement for wearing and binder courses - Putra Jaya, Ramadhansyah; Haryati, Yaacob; Chang, Fung-Lung; Mohd Rosli, Hainin; Ahmad Safuan, A. Rashid; Norhidayah, Abdul Hassan (Faculty of Engineering, Universitas Indonesia, 2018)
This study investigated the use of a shear box device to measure the bond condition between two layers of hot mix asphalt pavement: the wearing course and the binder course. The wearing course analysed was a Malaysian dense-graded asphaltic concrete mixture of nominal maximum aggregate 10 mm in size (AC10), which was applied over the binder course of another dense-graded asphaltic concrete mixture, AC28. A range of bond conditions was investigated by selecting various asphalt emulsions, application rates, and wearing course thicknesses based on the Malaysian standards of specification. Test results showed that interface shear strength increased as tack coat application rates and wearing course thicknesses increased. Among the tested asphalt emulsion types, a modified asphalt emulsion called RS2KL provided the highest shear resistance. Findings also show that a binder's complex shear modulus elastic portion (G*/sinδ) can affect interface shear strength for thin mixes at low rates of tack coat application.